Estimating a cost-effectiveness threshold for health care decision-making in South Africa - Edoka, Ijeoma P (Health Policy Plan, 2020)
Cost-effectiveness thresholds are important decision rules that determine whether health interventions represent good value for money. In low- and middle-income countries, the World Health Organization (WHO) one to three times per capita gross domestic product (GDP) per disability-adjusted life years (DALYs) averted has been the most widely used threshold for informing resource allocation decisions. However, in 2016, the WHO withdrew recommendations for using this threshold, creating a significant vacuum in South Africa and many countries that rely on results of cost-effectiveness analyses for making resource allocation decisions. This study estimates a cost-effectiveness threshold that reflects the health opportunity cost of health spending in South Africa using a three-step approach. First, marginal returns to health spending was estimated as health spending elasticity for crude death rates using a fixed effect estimation approach. Second, the opportunity cost of health spending was estimated as DALYs averted. Finally, a cost per DALY averted threshold was estimated as the inverse of the marginal product of health spending. We show that 1% of total health spending in 2015 (equivalent to approximately ZAR 1.54 billion/USD 120.7 million) averted 1050 deaths, 34 180 years of life lost, 5880 years lived with disability and 40 055 DALYs. The cost-effectiveness threshold was estimated at approximately ZAR 38 500 (USD 3015) per DALY averted, ∼53% of South Africa’s per capita GDP in 2015 (ZAR 72 700/USD 5700) and lower than the previously recommended one to three times per capita GDP. As South Africa moves towards implementing universal health coverage reforms through National Health Insurance by 2025, the adoption of a threshold that reflects health opportunity costs will be crucial for ensuring efficiency in the allocation of scarce resources. This study provides useful insight into the magnitude of the health opportunity cost of health spending in South Africa and highlights the need for further research.